Application of Fan sub-equation method to complex nonlinear time fractional Maccari system - N Kadkhoda (Mathematics and computational sciences, 2022)
In this study, the Fan sub-equation method is applied to study exact solutions of complexnonlinear time fractional Maccari system. Using this method, we obtain various solutions which thoseare useful t to understand better the concepts of the complicated physical phenomena. This method isstraightforward, and it can be used to many nonlinear equations.